Analisis Penguasaan Konsep Materi Senyawa Hidrokarbon Siswa Kelas XI SMA - Moh Musli Malajai; Masrid Pikoli; Mangara Sihaloho; Julhim S. Tangio; Ahmad Kadir Kilo; Haris Munandar (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to analyze students' conceptual mastery of hydrocarbon compounds. The method used in the study is descriptive qualitative. The study was conducted in the even semester of the 2023/2024 academic year. The subjects of this study were 59 students of class XI MIPA SMA Negeri 1 Limboto. The data collection technique used a concept mastery test instrument in the form of multiple choices that had been tested for validity and reliability. The results showed that conceptual understanding. The percentage of students in Determining the molecular formula and structure of hydrocarbon compounds obtained a percentage of 78.53% with a good category, on the indicator Distinguishing types of reactions and physical regularity of 67.80% with a sufficient category, on the indicator determining the isomers of hydrocarbon compounds of 40.68% with a less category, on the indicator analyzing the type of C atom based on the number of C atoms bound to the carbon atom chain of 27.12% with a less category, on the indicator predicting the type of isomers of hydrocarbon compounds, namely 38.42% with a less category and on the indicator correcting the structural formula of hydrocarbon compounds, namely 63.84% with a sufficient category. Then the total average percentage value is 52.73% with the Less category.